Different Seasonal Precipitation Anomaly Patterns in Central Asia Associated With Two Types of El Niño During 1891–2016 - Feng, Fan; Zhao, Yong; Huang, Anning; Li, Yang; Zhou, Xin (Frontiers in Earth Science, 2022)
In this study, we examine the different seasonal precipitation anomaly patterns in Central Asia associated with the cold-tongue (CT) El Niño and warm-pool (WP) El Niño from the El Niño developing autumn to the decaying spring based on the Global Precipitation Climatology Centre (GPCC) full data reanalysis version 2018 (GPCC V2018) data set. Overall, El Niño are associated with more precipitations over Central Asia, but significant discrepancies can be found in the precipitation anomaly spatial patterns associated with the two types of El Niño from the El Niño developing autumn to the decaying spring. The precipitation associated with CT El Niño is mostly concentrated in the plains and hilly areas of Central Asia and is more dispersed in space. Whereas the precipitation associated with WP El Niño is mostly concentrated along Pamirs and Tian Shan Mountains with consistency throughout the autumn before El Niño peaks to the spring when El Niño decays. Also, the strength of the positive precipitation anomaly associated with WP El Niño is significantly stronger than that of CT El Niño. The analysis of anomalous atmospheric circulation caused by two types of El Niño shows that the interconfiguration of anomalous high pressure in the south side of Central Asia at low and middle latitudes and anomalous low pressure and anomalous high pressure in the high latitudes of Eurasia affects the southwest water vapor flux and north side water vapor flux in Central Asia, thus causing different effects of different types of El Niño on precipitation in Central Asia at different stages. The spatial consistency of the WP El Niño effect on precipitation in Central Asia over three seasons may be related to the upward branch of the anomalous Walker circulation over the Indian Ocean induced by it.